Integrated hydrological modelling of wetlands for environmental management: the case of the Usangu wetlands in the Great Ruaha catchment - Kashaigili, Japhet J.; Mahoo, H.F.; McCartney, Matthew P.; Lankford, B.A.; Mbilinyi, B. P.; Mwanuzi, F. L. (2005)
Knowledge of wetland hydrology and quantification of water inputs and outputs are Prerequisites to understanding wetland environments and determining their vulnerability to change. To get a better understanding of the dynamics of wetland change in the Usangu Plains, a study was conducted to: a) investigate the effects of human interventions on the wetlands, and b) determine the amount of dry season inflow required to maintain environmental flows downstream of the wetlands. The study integrated hydrologic data, remote sensing and GIS techniques to study the dynamics and spatial response of the wetlands. A monthly water balance model was developed for the wetlands to determine the major components of the water budget. The results of the analyses indicate that the wetlands have changed appreciably in size over recent years and the inflow volumes have decreased with time as a result of increased human interventions. The dry season vegetated swamp cover, a major component of the swamp, decreased by 67% over the 16 years from 1984 to 2000. If this trend continues, it is possible that the wetlands will undergo a change which will be extremely difficult to reverse. Downstream of the wetlands an environmental flow of 0.5 m3/s was estimated. To maintain this outflow, the corresponding inflow volume into the wetlands was estimated to be 7m3/s. To achieve this, the available dry season water resource will have to be divided 20% for anthropogenic needs and 80% for the environment to feed the wetland. The study has demonstrated the need for integrated water resources management to balance the demands between different sectors and enable appropriate catchment interventions to ensure the sustainability of wetland resources.